European Academy of Neurology/European Alzheimer’s Disease Consortium position statement on diagnostic disclosure, biomarker counseling, and management of patients with mild cognitive impairment - Frederiksen, Kristian Steen; Nielsen, T. Rune; Winblad, Bengt; Schmidt, Reinhold; Kramberger, Milica G.; Jones, Roy W.; Hort, Jakub; Grimmer, Timo; Georges, Jean; Frölich, Lutz; Engelborghs, Sebastiaan; Dubois, Bruno; et al. (European journal of neurology, 2021)
Background and purpose Careful counseling through the diagnostic process and adequate postdiagnostic support in patients with mild cognitive impairment (MCI) is important. Previous studies have indicated heterogeneity in practice and the need for guidance for clinicians. Methods A joint European Academy of Neurology/European Alzheimer’s Disease Consortium panel of dementia specialists was appointed. Through online meetings and emails, positions were developed regarding disclosing a syndrome diagnosis of MCI, pre- and postbiomarker sampling counseling, and postdiagnostic support. Results Prior to diagnostic evaluation, motives and wishes of the patient should be sought. Diagnostic disclosure should be carried out by a dementia specialist taking the ethical principles of “the right to know” versus “the wish not to know” into account. Disclosure should be accompanied by written information and a follow-up plan. It should be made clear that MCI is not dementia. Prebiomarker counseling should always be carried out if biomarker sampling is considered and postbiomarker counseling if sampling is carried out. A dementia specialist knowledgeable about biomarkers should inform about pros and cons, including alternatives, to enable an autonomous and informed decision. Postbiomarker counseling will depend in part on the results of biomarkers. Follow-up should be considered for all patients with MCI and include brain-healthy advice and possibly treatment for specific underlying causes. Advice on advance directives may be relevant. Conclusions Guidance to clinicians on various aspects of the diagnostic process in patients with MCI is presented here as position statements. Further studies are needed to enable more evidence-based and standardized recommendations in the future.
"First published: 23 December 2020"
Gesehen am 20.11.2023